Perspectives in Quantun Hall effects: novel quantum liquids in low-dimensional semiconductor structures - Sarma, Sankar Das; Pinczuk, Aron (New York: John Wiley & Sons, 1997)
The discovery of the quantized and fractional Quantum Hall Effect phenomena is among the most important physics findings in the latter half of this century. The precise quantization of the electrical resistance involved in the quantized Hall effect phenomena has led to the new definition of the resistance standard and has metrologically affected all of science and technology. This resource consists of contributions from the top researchers in the field who present recent experimental and theoretical developments. Each chapter is self-contained and includes its own set of references guiding readers to original papers and further reading on the topic.
Localization, metal-insulator transitions, and Quantum-Hall effect -- Experimental studies of multicomponent Quantum Hall systems -- Properties of the electron solid -- Edge-state transport -- Multicomponent Quantum Hall systems: the sum of their parts and more -- Fermion Chern-Simons theory and the unquantized Quantum Hall Effect -- Composite Fermions -- Resonant inelastic light scattering from Quantum Hall systems -- Case for the magnetic-field-induced two-dimensional Wigner Crystal -- Composite Fermions in the Fractional Quantum Hall effect
Includes bibliography and index
Keywords: Quantum Hall Effect